Impact of on-farm Land Restoration Practices on the Time and Agency of Women in the Drylands of Eastern Kenya - Crossland, M.; Paez Valencia, Ana Maria (2020)
This brief describes implementation work under the ICRAF led project “Restoration of degraded land for food security and poverty reduction in East Africa and the Sahel: taking successes in land restoration to scale”. The project is an IFAD-EC funded initiative developing innovative ways to scale land restoration activities through embedding research in development. It does this by collaborating with development programs to systematically test promising restoration options across a range of contexts. In Kenya, the project is working with over 2000 farmers across Kitui, Makueni and Machakos counties to implement on-farm comparisons of various land restoration options, including different tree planting practices and the use of planting basins.